Revolutionizing university teaching: orientations, experiences and theories for the teaching practice in business - Gumieiro, Angela (Universidade Estadual de Campinas, 2019)
A review of the book “Revolutionized university teaching: guidelines, experiences and theories for teaching in business” is presented, organized by professors Gilberto José Miranda, Edvalda Araújo Leal and Silvia Pereira de Castro Casa Nova, in 2018, with the objective to address issues related to teacher education for university education, with regard to the methodology of higher education in business. Composed of twelve chapters divided into three parts, which address different dimensions of university teaching, proposing to reflect and bring together the extensive and rich human and research material on higher teaching in the business area.